Increasing Student Motivation by Using Problem-Based Learning of Maritime Contextual Problems in Lingga Regency in Mathematics Leaning at SMA Negeri 1 Lingga - Rachmi; Nevrita; Encik Abdulhajar; Zaitun (Raja Zulkarnain Education Foundation, 2025)
The implementation of the Independent Curriculum demands a transformation of the mathematics learning paradigm that emphasizes contextual experience through a problem-solving approach. The low motivation to learn mathematics of SMA Negeri 1 Lingga students, especially in statistics materials with achievements below the KKM (42.86% of students complete), indicates the need for innovative learning strategies that are relevant to the local context. This study aims to examine the effectiveness of Problem-Based Learning (PBL) based on maritime contextual problems in Lingga Regency in increasing the motivation to learn mathematics of grade X.1 students. The research method used the Kemmis and McTaggart model Classroom Action Research with two learning cycles over three weeks, involving 37 students selected through purposive sampling. Data were collected using a learning motivation questionnaire based on five indicators with a four-point Likert scale, then analyzed quantitatively descriptively. The results showed a significant increase in motivation scores from 3,249 (medium category) in the first cycle to 3,784 (high category) in the second cycle with an increase of 0.355 points. The contextualization of maritime issues using real data on sea transportation, fishermen's activities, and trade in marine products has succeeded in creating an authentic learning experience that bridges the gap between theoretical knowledge and practical applications. In conclusion, PBL based on the maritime context is effective in increasing students' learning motivation by transforming active participation, presentation courage, and development of independence. It is recommended that the systematic implementation of local context PBL as an alternative learning to increase student involvement in mathematics learning.